SPEECH ACTS IN "THE BORN LOSER" CARTOON STRIP IN THE JAKARTA POST DAILY NEWSPAPER - SANTIKO , RISMAN (2007)
This research is aimed at describing the types and intention of speech acts in The Born Loser cartoon strip. The object of the study is speech act utterances. The data are numerous discourse including speech act in the context of The Born Loser cartoon strip in the forms of dialogue that are taken from The Born Loser cartoon strip in the Jakarta Post daily newspaper. In collecting the data the writer uses observation and documentation method. The data are taken from The Born Loser cartoon strip in Jakarta Post daily newspaper issued in September and October 2006. In analyzing the types of speech acts of The Born Loser, the writer applied the theory of speech act of Searle. To describe the intention of The Born Loser, the writer also employs the speech act theory especially locution and illocut ion. The result of analysis shows that the types of speech act of The Born Loser is utterances, there are 22 utterances of representative, 13 utterances of directive, 10 utterances of expressive, and 2 utterances of commissive. Related to the meaning of the intention, it found that there are 12 utterances of requesting, and 5 utterances of suggesting. It can be concluded that the speaker's intention on The Born Loser is dominated by category of requesting.